2009
DOI: 10.1002/ppul.20985
|View full text |Cite
|
Sign up to set email alerts
|

A survey of once‐daily dosage tobramycin therapy in patients with cystic fibrosis

Abstract: The purpose of this study was to quantify the prevalence of once-daily dosage of tobramycin (ODDT) among Cystic Fibrosis Foundation-accredited care centers and affiliated programs (CFFACCs) and characterize the ODDT approaches used by these institutions. An anonymous cross-sectional survey of CFFACCs was performed using an electronic survey tool. This tool was electronically mailed to the program directors. Eighty-four out of 195 institutions completed the survey (response rate = 43%). Fifty-one (61%) of 84 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…4 According to recent surveys, the most commonly used intravenous antipseudomonal antibiotic classes were beta-lactams (98%) and aminoglycosides (61%-94.3%). [5][6][7] These surveys also elicited interesting results regarding the dosage strategies currently used by care centers. [5][6][7] Previous surveys of CF centers revealed that recommended doses and dosage regimens are not used by a substantial number of CF centers despite CFF, European, and UK CF Trust Working Group recommendations, and literature confirming the efficacy and safety of larger than Food and Drug Administration-approved doses for beta-lactam agents and once-daily aminoglycosides.…”
Section: Introductionmentioning
confidence: 99%
“…4 According to recent surveys, the most commonly used intravenous antipseudomonal antibiotic classes were beta-lactams (98%) and aminoglycosides (61%-94.3%). [5][6][7] These surveys also elicited interesting results regarding the dosage strategies currently used by care centers. [5][6][7] Previous surveys of CF centers revealed that recommended doses and dosage regimens are not used by a substantial number of CF centers despite CFF, European, and UK CF Trust Working Group recommendations, and literature confirming the efficacy and safety of larger than Food and Drug Administration-approved doses for beta-lactam agents and once-daily aminoglycosides.…”
Section: Introductionmentioning
confidence: 99%
“…8 Further comparing these data with pediatric CF program data collected as part of this study (following the release of the Cystic Fibrosis Foundation pulmonary exacerbation guidelines) indicates that the use of EID is essentially the same in pediatric and adult CF programs across the United States. 19 That said, the overall use of this regimen in the adult CF population is likely more common because the use of EID in pediatric CF varies based on age with its use being most common in adolescents and least common in younger pediatric patients, and because a higher percentage of adult CF programs frequently or always use EID.…”
Section: Discussionmentioning
confidence: 99%
“…8 This follow-up survey indicates that the vast majority of adult CF programs (94%) now use EID (as once-daily or twice-daily dosing) in the treatment of pulmonary exacerbations, with 83% of adult CF programs using once-daily EID exclusively. That noted, the percentage of adult CF programs reporting the use of once-daily EID may better reflect current EID practices because a twice-daily dosing approach may not have been considered to be EID by all respondents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations